PENDEKATAN SINTAGMATIK PARADIGMA DALAM KAJIAN BAHASA - Zainuddin Zainuddin (BAHAS, 2020)
Abstract This study discusses the syntagmatic and paradigmatic phenomena in language studies. In other words, this study is a syntagmatic and paradigmatic relation in language studies. The syntagmatic and paradigmatic relations are based on 2 (two) aspects of language phenomena, namely 1. Intralinguistic aspects and 2. Extralinguistic aspects. In the intralinguistic aspects of syntagmatic and paradigmatic relations, language units are analyzed at the phonological, morphological, and syntactic levels. Whereas in extralinguistic analysis the syntagmatic and paradigmatic meanings of phonological internal units of the word (phoneme) and segmentation of morphological units in morphological processes (morpheme and afix) in syntactic units. In other words, syntagmatic and paradigmatic ideas (notion) linked to lingual elements or units of language can be distinguished that in a syntagmatic and paradigmatic process where syntagmatic relations are horizontal (semantic) meanings. Whereas the paradigmatic relation is a form relation or vertical relation. With the understanding that the syntagmatic relationship is the representation relationship (horizontal) and the inabsentia relationship is the vertical relationship. Keywords: syntagmatic, paradigmatic, language. Abstrak Kajian ini membahas tentang fenomena sintagmatik dan paradigmatic dalam kajian bahasa. Dengan kata lain kajian ini merupakan relasi sintagmatik dan paradigmatik dalam kajian bahasa. Relasi sintagmatik dan paradigmatik berdasarkan pada 2 (dua) aspek fenomena bahasa yaitu 1. Aspek intralinguistik dan 2. Aspek ekstralinguistik. Pada aspek intralinguistik relasi sintagmatik dan paradigmatik dianalisis satuan-satuan bahasa pada tataran fonologi, morfologi, dan sintaksis. Sedangkan pada ekstralinguistik dianalisis makna sintagmatik dan paradigmatik pada satuan-satuan internal kata secara fonologis (fonem) dan segmentasi atas satuan morfologis dalam proses morfologis (morfem dan afix) dalam satuan sintaksis. Dengan kata lain, gagasan (notion) sintagmatik dan paradigmatik yang ditautkan dengan unsur-unsur atau satuan lingual kebahasaan dapat dibedakan bahwa dalam proses sintagmatik dan paradigmatik dimana relasi sintagmatik adalah relasi makna (semantik) secara horizontal. Sedangkan relasi paradigmatik adalah relasi bentuk atau relasi vertikal. Dengan pengertian bahwa hubungan sintagmatik adalah hubungan inpresentia (horizontal) dan hubungan inabsentia yaitu hubungan vertikal.Kata kunci: sintagmatik, paradigmatik, bahasa.